PERAN KEPALA DESA DAN BADAN PERMUSYAWARATAN DESA DALAM MENERAPKAN SANKSI TENTANG PENERTIBAN HEWAN DI DESA PARABUBU KECAMATAN MEGO KABUPATEN SIKKA - Danar Aswim; Abdullah Muis Kasim; Osni Osalia Wonga (Sekolah Tingi Keguruan dan Ilmu Pendidikan (STKIP) PGRI Tulungagung, 2022)
The research aims to find out the role of the village head and BPD in implementing sanctions on animal control in Parabubu Village, Mego Subdistrict, Sikka Regency To find out the effectiveness of the Village Head and the Village Consultative Agency in implementing animal control sanctions in Parabubu Village, Mego Subdistrict, Sikka Regency. Research methods use descriptive qualitative with data collection methods using through observation, interviews, and documentation. While data analysis uses data reduction analysis, data presentation, and data verivikasi. The results of the study are as follows: The role of the Village Head and BPD in implementing sanctions on animal control in Parabubu Village is carried out in several ways including maximizing the role of the Village Head as a policy maker, rule maker, as a motivator, increasing community participation. The effectiveness of the Village Head and BPD can be said to be effective in implementing animal control sanctions.Keywords: Role of Village Chief, BPD, Public Figure, and Animal Control Sanctions